Impact of temperature, nutrients, pH and cold storage on the germination, growth and resistance of Bacillus cereus spores in egg white. (April 2018) - Soni, Aswathi; Oey, Indrawati; Silcock, Patrick; Bremer, Phil J.
Abstract: B. cereus spores are a concern to the food industry, especially to the producers of heat sensitive food products like egg white or precooked and stored food such as fried rice. This study investigated the impact of nutrients, temperature (4, 8, 15 and 25 °C), pH (4, 5, 7 and 9), and cold storage on the germination, growth and resistance of B. cereus spores. In egg white held at 4 °C for 12 days spore germination was not apparent, however the addition of egg yolk (5%) resulted in a 2 Log colony forming units (CFU)/mL increase in vegetative cells (p < .05). Addingl -alanine (0.9 mg/mL) to egg white did not induce germination unless the spores were simultaneously heat activated at 70 °C for 30 min. On incubation at 15 or 25 °C in egg white, spore germination increased by 3.0 Log and 3.7 Log CFU/mL on day 12. The presence of 5% yolk further enhanced germination and subsequent sporulation during storage at 15 and 25 °C. Acidification (pH 4) of 10% egg white solution prevented germination at 4, 8, 15 and 25 °C. Spores held at 4 °C for 6 days in phosphate buffer (50 mM, pH 4) had visible deformations on their surface (scanning electron microscopy) and a significant reduction in D88, and D92 values of 13.9 and 8.2 min respectively. A better understanding of how spores sense and respond to changing environmental conditions will help in the development of processing strategies, involving multiple hurdles to ensure the prevention of germination and subsequent toxin production. Graphical abstract: Image 1 Highlights: B. cereus spores do not germinate at 4 °C in egg white. Presence of yolk in egg white enhances germination at 4, 8, 15 and 25 °C. pH 4 inhibits germination of B. cereus spores at 4, 8, 15 and 25 °C. D-values of B. cereus spores reduce while held at 4 °C for 6 days.